Peran Literasi Keuangan Dalam Mendorong Efektivitas Pemanfaatan Dana Program Keluarga Harapan (PKH) dan Memperkuat Ketahanan Ekonomi Keluarga - Gina Himmatul Aliyah; Kurniawan Kurniawan; Edi Fitriana Afriza (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This research is motivated by the low level of financial literacy in encouraging the effective utilization of Family Hope Program (PKH) funds and strengthening the economic resilience of beneficiary families in Purbaratu District, Tasikmalaya City. The research used a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observation, and documentation with three primary informants of PKH beneficiary families and supporting informants, namely one PKH Facilitator and three government agencies. The results of the study indicate that the level of financial literacy of beneficiary families still varies, especially in aspects of financial planning, expenditure management, and savings habits. Utilization of PKH funds is generally focused on meeting education, health, and basic household needs. Financial literacy plays an important role in helping families manage assistance funds more effectively, thereby strengthening family economic resilience. However, there are still obstacles such as low income, minimal understanding of financial management, and consumptive behavior that affect the effectiveness of PKH fund utilization.